2009
DOI: 10.1088/0004-637x/705/1/199
|View full text |Cite
|
Sign up to set email alerts
|

The LICK AGN MONITORING PROJECT: BROAD-LINE REGION RADII AND BLACK HOLE MASSES FROM REVERBERATION MAPPING OF Hβ

Abstract: We have recently completed a 64-night spectroscopic monitoring campaign at the Lick Observatory 3-m Shane telescope with the aim of measuring the masses of the black holes in 12 nearby (z < 0.05) Seyfert 1 galaxies with expected masses in the range ∼ 10 6 -10 7 M ⊙ and also the well-studied nearby active galactic nucleus (AGN) NGC 5548. Nine of the objects in the sample (including NGC 5548) showed optical variability of sufficient strength during the monitoring campaign to allow for a time lag to be measured b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
506
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 417 publications
(533 citation statements)
references
References 72 publications
25
506
2
Order By: Relevance
“…Added to this uncertainty is the fact that AGN variations are stochastic and not guaranteed to occur during the course of a monitoring campaign for any particular AGN of interest (cf. the case of Mrk 290 which was monitored in 2007 and showed strong variations as reported by Denney et al 2010, but according to Bentz et al 2009b showed little to no variation when it was monitored again in 2008). The typical warning for the stock market also applies here: past performance is no guarantee of future behavior.…”
Section: Reverberation Mapping Primermentioning
confidence: 58%
See 3 more Smart Citations
“…Added to this uncertainty is the fact that AGN variations are stochastic and not guaranteed to occur during the course of a monitoring campaign for any particular AGN of interest (cf. the case of Mrk 290 which was monitored in 2007 and showed strong variations as reported by Denney et al 2010, but according to Bentz et al 2009b showed little to no variation when it was monitored again in 2008). The typical warning for the stock market also applies here: past performance is no guarantee of future behavior.…”
Section: Reverberation Mapping Primermentioning
confidence: 58%
“…While the agreement is reassuring for these two objects, a sample of two is hardly definitive. Two more AGNs with reverberation masses -NGC 6814 (Bentz et al, 2009b) and NGC 5273 (Bentz et al, 2014) -are in various stages of the dynamical modeling process, and a handful of other AGNs are being targeted for reverberationmapping with the hope of dynamical modeling to follow. Fig.…”
Section: Black Hole Massesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although active galaxies with measured reverberation black hole masses seem to follow the same M BH -σ relation as non-AGN galaxies (Gebhardt et al 2000b;Ferrarese et al 2001), it has not been clearly shown whether the M BH -σ relation of active galaxies has the same slope and scatter, due to the limited sample size and the black hole mass range of the local AGNs with reliable reverberation mass and stellar velocity dispersion measurements. Recently, Bentz et al (2009b) reported new reverberation measurements for a sample of eight local Seyfert galaxies, and stellar velocity dispersions of these galaxies were measured by Woo et al (2009). The MBH -σ relation of active galaxies in the present-day universe from Woo et al (2009).…”
Section: The Present-day M Bh -σ Relation For Active Galaxiesmentioning
confidence: 99%